Design and operation of a double-fiber displacement sensor - Golnabi, H.; Azimi, P. (Optics communications, 2008)
Design and operation of a double-fiber sensor for displacement measurements are reported in this study. In this arrangement, one fiber transmits the laser light to the target and the second one receives the light reflected off the target and transmits to a photodetector. Utilizing inexpensive plastic optical fibers offers advantages such as higher reflexability and more robustness at a reasonable cost, which are required for some applications. The novelties of the reported design are compactness of the fiber probe, flexibility, long dynamic range (22 mm), and it is possible to use the source and the detector at the same side. The displacement of the target causes the intensity modulation and such a power variation is the base of sensor operation. Measurements for the metallic and non-metallic surfaces are performed and the results for aluminum, copper, and bronze sheets are presented here. Our results indicate that the sensitivity is highest for the plane mirror (288.8 mV/mm), high for the shiny metallic surfaces (230.6 mV/mm), but it can be used for other surfaces with a reasonable sensitivity. Important parameters of the sensor such as reproducibility (1.0%) and hysteresis effect (1.8%) are also investigated for this device. The theoretical formulation of the sensor operation is also developed and the computed results are compared with the experimental ones. The obtained experimental respond curve agrees well with the theoretical one, which verifies the successful operation of the proposed sensor system for precise displacement measurements.